Pagan and Christian in an age of anxiety : some aspects of religious experience from Marcus Aurelius to Constantine - Dodds, E. R. (Eric Robertson), 1893-1979 (Cambridge : Cambridge University Press, 1968)
Dodds examines the personal religious attitudes and experiences common to pagans and Christians in the period between Marcus Aurelius and Constantine.
Preface; Key to references; 1. Man and the material world; 2. Man and the daemonic world; 3. Man and the divine world; 4. The dialogue of paganism with Christianity; Index.
The Wiles lectures given at the Queen's University, Belfast, 1963.